Ius Constituendum Restorative Justice in Indonesia - Benny Elfian Syah; Didik Endro Purwoleksono (Media Iuris, 2023)
In recent times, legal experts in Indonesia have engaged in widespread discussions on restorative justice. This is because the country’s criminal justice system has been unable to deliver justice to society, with many cases deemed unworthy of trial, let alone convictions and sentencing. Most institutions that make up the criminal justice system, including the police, prosecutors’ offices, and courts, cannot be held solely responsible for this issue as they simply enforce existing regulations. Therefore, a new approach is necessary to resolve cases that prioritize mediation to reach a consensus based on social justice values, in which the concept of restorative justice plays a role. Restorative justice is not a new concept as it has been used by society for hundreds of years to solve problems that are not in line with social norms. Many customary practices prioritize technical solutions through local wisdom and emphasize forgiveness. Such practices include Gotong Royong, Tepo Seliro, Tego Lorone Gak Tego Patine, and others, all of which are foundational to society’s way of thinking about problem-solving. Based on these basic norms, Indonesian Founding Fathers incorporated these practice into Principles 2, 4, and 5, which are part of the Pancasila (Five Principles of Indonesian) norm. However, law enforcement may not fully understand these basic norms while implementing them. To anticipate the existing concept, criminal justice system institutions have created rules that are yet to reflect the approach of restorative justice. These institutional rules appear poorly integrated, potentially leading to normative conflicts that ultimately result in uncertainty within the criminal justice system.